Sistem Pendukung Keputusan Pemberian Kredit Dengan Metode Perbandingan Eksponensial (MPE). (Studi Kasus: KSPPS Aneka Dana Syariah) - Yanuar Muhammad Fadli; Andriani Kusumaningrum; Bebas Widada (Redtech Putra Benua, 2024)
KSPPS Aneka Dana Syariah Surakarta is a business entity or organization owned and operated by its members to fulfill common interests in the field of savings and loans. The main problem in this research is that there is an increase in the number of prospective customers who wish to apply for motorbike loans at KSPPS Aneka Dana Syariah. In the old system that has been running in determining prospective customers based on one capital criterion and ignoring other criteria such as: Character, Capacity, Capital, Collateral and Condition, so that the decision results are not quite right. The purpose of this study is to create a decision support system for selecting prospective customers using the Exponential Comparison Method. This method was chosen because it can carry out a ranking process based on criteria and weights and is able to determine the best alternative. The method in this research is through interviews, observation, and literature study. System design is made with diagrams, Hierarchy Input Process Output, Diagram Arus Data, relationships between tables and database design. The system is created in a program with the PHP programming language. The end result of this application program is a prospective customer report, the overall selection report and the best selection report. The results of functional testing by black-box method showed that the system ran as expected and the functions of the application ran properly. The results of testing the system that has been carried out obtained valid results.